2014
DOI: 10.1073/pnas.1413216111
|View full text |Cite
|
Sign up to set email alerts
|

Ligand- and mutation-induced conformational selection in the CCR5 chemokine G protein-coupled receptor

Abstract: We predicted the structural basis for pleiotropic signaling of the C-C chemokine type 5 (CCR5) G protein-coupled receptor (GPCR) by predicting the binding of several ligands to the lower-energy conformations of the CCR5 receptor and 11 mutants. For each case, we predicted the ∼20 most stable conformations for the receptor along with the binding sites for four anti-HIV ligands. We found that none of the ligands bind to the lowest-energy apo-receptor conformation. The three ligands with a similar pharmacophore (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 28 publications
3
41
0
Order By: Relevance
“…2B and 3E). The multiplicity of unliganded forms of CCR5 is consistent with previous computational analyses that predicted the existence of several apo forms of CCR5 with different stabilities (33). The coexistence of several dimeric conformations is also consistent with a single-molecule fluorescence imaging study that showed preformed diverse dimeric structures of another class A GPCR (11).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…2B and 3E). The multiplicity of unliganded forms of CCR5 is consistent with previous computational analyses that predicted the existence of several apo forms of CCR5 with different stabilities (33). The coexistence of several dimeric conformations is also consistent with a single-molecule fluorescence imaging study that showed preformed diverse dimeric structures of another class A GPCR (11).…”
Section: Discussionsupporting
confidence: 89%
“…Small-molecular weight ligands can act as pharmacological chaperones by rescuing the delivery of poorly trafficked, disease-causing GPCRs (31,32). We tested the effect of MVC, which is a partial inverse agonist of CCR5 (33,34), on the cell surface delivery of CCR5 dimerizationcompromised mutants. We hypothesized that this compound might stabilize a conformation of the receptors suitable for export from the ER.…”
Section: Mvc As a Pharmacological Chaperonementioning
confidence: 99%
“…To predict the 3D structures of hSSTR5, we developed a modified version of G PCR En semble of S tructures in M embrane B i L ayer E nvironment (GEnSeMBLE)10 complete sampling computational method, which aims to predict the 10 to 25 lower‐energy protein structures likely to play a role in activation upon binding various ligands. GEnSeMBLE has been successfully applied in the prediction of inactive‐state structures of GPCRs such as cannabinoid receptor type 1 (CB1),8a adenosine A3 receptor (hAA 3 R),8c olfactory receptor OR1G1,8d bitter taste receptor Tas2R38,8e the GLP‐1 receptor (GLP1R),8f and C‐C chemokine receptor type 5 (CCR5) 8g. For CB1 and hAA 3 R, the active states were also identified successfully.…”
Section: Introductionmentioning
confidence: 99%
“…Mutation-induced conformational change and induced fit with the ligand are the key factors of protein–ligand interactions in cancer cells (2,3). Point mutations at spatially distinct sites lead to conformational changes and exert hinge effects (4).…”
Section: Introductionmentioning
confidence: 99%